The Study on Media Access Control Protocol for Wireless Network in Library. (30th August 2015) - Zeng, Wen; Zhang, Junsheng; Li, Ying; Qu, Peng
Wireless technology will be widely used in libraries with the development of the mobile network in the near future. This paper focuses on MAC protocol for wireless network based on ultra-wideband band (UWB) to solve the problems of real-time and reliability in the wireless transmitting. According to the particular signal characteristics such as low energy consumption and excellent location, we propose a multichannel MAC protocol (UWBIMAC) based on status-adaptive to choose the channel mechanism. Simulation results show that the protocol had the ability of stronger antijamming, improved network throughput, and provided better average delay performance than IEEE802.15.4 MAC, IEEE802.11 MAC, and other UWBIMAC protocols. This method could be used in the process of wireless transmission service in the library or other similar scenarios. To a certain extent, it solves the problem of real-time and reliable performance in the process of wireless communication.